Covid-19: Lip gloss and the threat to women's sport - Davis, P.; Weaving, C. (Philosophical Perspectives on Pandemic Sport, 2021)
The COVID-19 pandemic has thrown social inequalities into sharp relief and is therefore likely to evolve into a point of sociocultural articulation and resolution. One such enduring inequality is male and female sport, an inequality undetachable from broader sex inequality. While men`s sport has suffered during the pandemic, women`s sport has suffered significantly more in terms of a thicket of features such as access, support structures, finance, media and gender ideology. Without robust post-pandemic responses that prioritize female sport voices, the progress made by women`s sport threatens to be dramatically reversed. Many girls, furthermore, may struggle to return to recreational sport (or return to their former extent) when the conditions of the pandemic are over. The critique of and prescriptions for the preceding disparities can use insights from Liberal Feminism, with its themes of equal access and status; Radical Feminism, with its themes of epistemic and political authority for women; and Marxist Feminism, with its theme of gendered economic inequality.